2007
DOI: 10.1890/06-0990
|View full text |Cite
|
Sign up to set email alerts
|

Fragmention by Agriculture Influences Reproductive Success of Birds in a Shrubsteppe Landscape

Abstract: Shrubsteppe communities are among the most imperiled ecosystems in North America as a result of conversion to agriculture and other anthropogenic changes. In the Intermountain West of the United States, these communities support a unique avifauna, including several species that are declining and numerous others that are of conservation concern. Extensive research in the eastern and central United States and in Scandinavia suggests that fragmentation of formerly continuous forests and grasslands adversely affec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 57 publications
1
29
1
Order By: Relevance
“…Similarity between the daily nest survival rate found here and daily nest survival rates of songbirds in sagebrush habitat calculated in other fragmented landscapes with negative population growth (Vander Haegen 2007) suggests that reproduction in the Okanagan area is insufficient to maintain songbird populations in sagebrush habitat. Negative population trends have been detected in the study region for all four songbird species studied here, and edge effects on reproduction may be contributing to these declines (Sauer et al 2014).…”
Section: Discussionsupporting
confidence: 78%
See 4 more Smart Citations
“…Similarity between the daily nest survival rate found here and daily nest survival rates of songbirds in sagebrush habitat calculated in other fragmented landscapes with negative population growth (Vander Haegen 2007) suggests that reproduction in the Okanagan area is insufficient to maintain songbird populations in sagebrush habitat. Negative population trends have been detected in the study region for all four songbird species studied here, and edge effects on reproduction may be contributing to these declines (Sauer et al 2014).…”
Section: Discussionsupporting
confidence: 78%
“…The edge effect on nest abundance in orchard edge habitat appears to be due to edge avoidance: individuals, particularly Vesper and Brewer's Sparrows, do not occupy orchard edge habitat as frequently as interior habitat, and so the relative abundance of nests found in orchard edge habitat is also lower. Grassland songbirds have varied responses to the presence of edges (Helzer andJelinski 1999, Ribic et al 2009), but birds in sagebrush shrubsteppe generally show sensitivity to habitat fragmentation (Knick and Rotenberry 1995, Ingelfinger and Anderson 2004, Vander Haegen 2007. Songbirds likely avoid edges with stronger vegetative contrast, and songbirds in sagebrush habitat in the study region have previously been shown to avoid areas with high tree density (Krannitz 2007).…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations